Otwarta arena. Spór o corridę de toros w Hiszpanii. Perspektywa socjologiczno-antropologiczna - Ziółkowska-Kuflińska, Magdalena (Wydawnictwo Naukowe UAM, 2016)
Książka ukazuje corridę de toros – hiszpańską tradycję, w szerokim kontekście społeczno-kulturowym. Autorka przybliża toczący się od lat w hiszpańskim społeczeństwie dyskurs publiczny wokół widowisk tauromachiach. W publikacji przedstawiono narrację, którą posługują się zarówno przeciwnicy, jak i zwolennicy corridy de toros, osadzoną w kontekście politycznym, społecznym i kulturowym. Dla polskiego czytelnika interesujący może być nie tylko sam opis kontrowersyjnej tradycji, ale również kierunki, w których owa tradycja ewoluuje. Praca jest efektem wieloletnich badań terenowych oraz wnikliwej analizy hiszpańskiej prasy.

The book presents the Spanish tradition corrida de toros in a broad social and cultural context. On the one hand, it provides a very detailed ethnographic account of this cultural phenomenon. On the other, it presents the ongoing public debate on tauromachic shows engaging Spanish society for many years. This publication relates and also provides an interpretation of the narratives of both opponents and supporters of corrida de toros. These two narratives have been placed in the political, social, cultural and ethical context. What might be interesting for the (Polish) reader is not only the actual description of this controversial tradition, but also the various ways it has evolved. This book is based on years of longitudinal field research, as well as an in-depth analysis of the Spanish press.
Keywords: hiszpańska korrida; widowiska tauromachiach; hiszpańska tradycja